1988
DOI: 10.1159/000111949
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Oligodendrocyte Remyelination following Injection of Cultured Central Nervous System Cells into Demyelinating Lesions in Adult Central Nervous System

Abstract: Following the injection of central nervous system (CNS) cell cultures, prepared from 1-day-old rats and maintained in vitro for 7 days, into irradiated, demyelinating lesions in the spinal cord of adult isologous animals, extensive remyelination of axons by oligodendrocytes was observed. In addition, astrocytes, within the transplanted cell suspension, established normal relationships with oligodendrocytes, axons and other tissue elements, which led to the establishment of large CNS territories throughout the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
0
1

Year Published

1992
1992
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(45 citation statements)
references
References 19 publications
6
38
0
1
Order By: Relevance
“…The loss in oligodendrocytes, observed in GCV programs P1-P7, P7-P14, and P14 -P21, agrees well with data available from the literature on oligodendrocyte proliferation in rat and mouse postnatal development in vivo (Gilmore, 1971;Skoff et al, 1976;Sturrock and McRae, 1980;Arenella and Herndon, 1984;Blakemore and Crang, 1988;Fok-Seang and Miller, 1994;Skoff et al, 1994). More than 70% of oligodendrocytes are formed during the first 2 weeks, and the rest are formed during the third postnatal week.…”
Section: Oligodendrocyte Apoptosis and Dysmyelination In Gcv-treated supporting
confidence: 87%
“…The loss in oligodendrocytes, observed in GCV programs P1-P7, P7-P14, and P14 -P21, agrees well with data available from the literature on oligodendrocyte proliferation in rat and mouse postnatal development in vivo (Gilmore, 1971;Skoff et al, 1976;Sturrock and McRae, 1980;Arenella and Herndon, 1984;Blakemore and Crang, 1988;Fok-Seang and Miller, 1994;Skoff et al, 1994). More than 70% of oligodendrocytes are formed during the first 2 weeks, and the rest are formed during the third postnatal week.…”
Section: Oligodendrocyte Apoptosis and Dysmyelination In Gcv-treated supporting
confidence: 87%
“…7). In no parts of the lesion were astrocytes seen forming a fine network of astrocyte processes between axons, as has been described following transplantation of mixed central glial cell sus pensions [7,15]. In the 2 control animals there were no glial cells within the lesion, which had an appearance that was consistent with that previously described for the Xirradiated ethidium bromide lesion [14,15],…”
Section: Interactions Between Astrocytes and Schwann Cellssupporting
confidence: 75%
“…GFAP + /A2B5-were identified as type 1 astro cytes [6], L l+/S100+ cells as Schwann cells [10], and intensely fibronectin f cells as meningeal cells [11]. A2B5, 04 and anti-Gal C were used to identify cells of the 0-2A lineage [12,13], Persistent glial-free CNS lesions were prepared in 7 adult PVG-Ola rats by local exposure of the spinal cord to 40 Gy of X-irradiation 3 days prior to induction of a demyelinating lesion [14,15], Dcmyelinating lesions were produced under halothanc anaesthesia by injecting 1 pi of 0.1% ethidium bromide (in normal saline) into the dorsal funiculus of the spinal cord following a laminectomy of the first lumbar vertebra. After a further 3 days 1 pi of cell suspension in MEM-HEPES was injected into the lesions of 5 rats.…”
Section: A Te Ria Ls and M E T H O D Smentioning
confidence: 99%
“…Transplanted rodent oligodendrocytes and their precursor cells as well as stem cells can myelinate axons in myelindeficient or demyelinated animals (12)(13)(14)(15)(16)(17)(18)(19). Recent studies have shown that transplantation ofearly passages of OPs (20) expanded in the presence of growth factors or immortalized with a conditional oncogene (21), resulted in myelination of naked axons within an irradiated and chemically induced spinal cord lesion in adult rats.…”
Section: Introductionmentioning
confidence: 99%
“…An understanding of these molecular mechanisms could be approached by using a growth-factor-dependent cell line in which gene transfer or targeting could be performed and tested in a transplantation paradigm. In addition, such myelin-forming cell lines could be used to explore ways to experimentally correct genetic defects identified in several inherited dysmyelinating diseases and leukodystrophies of animals and humans (10, 11).Transplanted rodent oligodendrocytes and their precursor cells as well as stem cells can myelinate axons in myelindeficient or demyelinated animals (12)(13)(14)(15)(16)(17)(18)(19). Recent studies have shown that transplantation ofearly passages of OPs (20) expanded in the presence of growth factors or immortalized with a conditional oncogene (21), resulted in myelination of naked axons within an irradiated and chemically induced spinal cord lesion in adult rats.…”
mentioning
confidence: 99%